DEVELOPMENT OF INFORMATION SYSTEM VR 360PoP TOUR TOURISM OF LAMPUNG - Ovi Dyantina; Davit Kurniawan; Firdaus Chaniago (Proceeding International Conference on Information Technology and Business, 2017)
Virtual Reality (VR) is a technology that allows users to interact with a computer-simulated environment. Currently VR is used for online or offline games but actually VR can be applied in various fields, such as tourism in Lampung Province. As a province which has many nature and interesting place, various food and culture, Lampung Province is one of great place for tourism. With VR 360PoP, users in Indonesia or around the world can choose the tourism place that they want after view (touring) the whole place. User get more information about the tourist destination and get help with the comparison of tourist types, tourist facilities and tourist environment that provided on the website. So, with this website make it easier for people who want to traveling in Lampung Province and also it become an opportunity in improving the economy of local residents and citiesKey Worlds : Virtual Reality, Camera 360PoP, Computer Vision, Tourism, Website.